A Technique for the Reconstruction of the Limbs of Osteomuscular Tissue Donors - Vialle,Luiz Roberto Gomes (2020)
Abstract The donation of bone and tendon tissues is an important source of biological material used in several surgical techniques. The removal of such tissues generates an important aesthetic sequel in the donor that requires limb reconstruction before returning the corpse to the relatives. The technique used by the Banco de Ossos do Paraná (Bone Bank from Paraná), Brazil, employs metal rebar, silicone tubes and nylon clamps to rebuild the limbs, it is easy to perform and has satisfactory aesthetic results.